2017
DOI: 10.3126/njog.v11i2.17450
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Cuff Dehiscence after Hysterectomy and One Minute Technique of Laparoscopic Vault Closure

Abstract: Aims: This study was done to observe the rate of vaginal cuff dehiscence of one minute technique of laparoscopic vault closure in laparoscopic hysterectomy.Methods: It was a descriptive study performed in Birat Hospital among 1012 patients undergoing total laparoscopic hysterectomy for both benign and malignant gynaecological conditions between 2012 to 2013. Monopolar cautery was used for laparoscopic colpotomy and vault was closed by laparoscopic single running suture, that is, one-minute laparoscopic vault c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
4
2
0
Order By: Relevance
“…Vaginal hysterectomy was chosen for cases with prolapse in 6% of cases. This observation is comparable to those of previous studies conducted in different countries 6,8,11,12,14 . 70.6% of our patients had no immediate or late post operative morbidity.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Vaginal hysterectomy was chosen for cases with prolapse in 6% of cases. This observation is comparable to those of previous studies conducted in different countries 6,8,11,12,14 . 70.6% of our patients had no immediate or late post operative morbidity.…”
Section: Discussionsupporting
confidence: 91%
“…The rest had a variety of complications listed in table 4. The commonest morbidities noted were anemia and post operative wound infection, this is similar to the findings of other studies 8,11,12 . One case of ureteric injury following an abdominal hysterectomy and bladder injury following a vaginal hysterectomy, this was lower than the 2.58% reported in other studies 10,13,14,15 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…If we can overcome this hurdle, there is a great place for laparoscopic hysterectomy, as seen in the study by Karki et al, where he reported 1012 cases of TLH in two years, from a private institute in eastern Nepal. 17 This disparity was also seen in the study from Finland (n=10,110) where the rate of Laparoscopic hysterectomy was high in a private hospital (LH=67%) compared to the local hospital (LH 19%). 6 Abdominal hysterectomy remains the common route ranging from 47.8% to 83.6%.…”
Section: Discussionmentioning
confidence: 88%